Kajian Semiotik: Perspektif Kesetaraan Gender Dalam Kepemimpinan Pada Tafsir Al-Misbah Dan Al-Azhar - Ira Nazhifatul Qolbah; Wildan Taufik; Dadan Rusmana (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to examine the views of Indonesian scholars, namely Muhammad Quraish Shihab and Buya Hamka, regarding gender equality between men and women. Of course, this study is motivated by the fact that men get a position above women in all fields. For decades, this patriarchal culture has always been a reference point and has ruled out the gender of a woman in working or playing an important role both internally and externally. the researcher tries to dismantle and peel from an Indonesian mufasir by using a comparative study between two great scholars, namely Hamka with his interpretation of al-Azhar and Qurais Shihab his work Al-Misbah by relating the gender relations of women in the scope of leadership in the Koran by using analysis semiotics on the theory of Charles Pierce). This study uses the method of interpreting muqarin between the interpretations of al-misbah and al-Azhar and is a type of qualitative research that uses library research. The results of this study are: (1) Quraish Shihab also considers that gender equality in leadership in Surat ann-Anisa verse 34 is not about male leadership in all matters (including social and political) over women, but rather about male leadership over women in the household. This means that using this verse as a prohibition against women to lead in politics is not correct. Looking at the context and the munasabah of the verse, namely about household relations. This seems to support the opinion of Quraish Shihab. (2) Buya Hamka's interpretation that in surah an-Nisa verse 34, says that the relationship between men and women is not equal.